Adolescents' Coping Strategies To Adapt To High-Risk Sexual Behavior Urges In Boarding Houses - Sinthia Rosanti Maelissa; Dian Thiofany Sopacua (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2025)
The current adolescent environment increasingly offers many choices. Dating styles that open up opportunities for risky sexual behavior seem to be an attractive offer, especially for adolescents who live in boarding houses. Living in boarding houses without direct supervision from parents and boarding house owners makes adolescents free to do anything, including risky sexual behavior with their boyfriends. This makes boarding houses a dangerous environment for adolescents who live there. This study uses a Descriptive Phenomenology Design, which aims to study in depth how adolescents use coping strategies to adapt to the urge to have risky sexual behavior in boarding houses. Six participants were selected using a purposive sampling technique for this study. The analysis in this study used the Colaizzi method. The results of this study yielded four themes, namely: 1) setting boundaries for dating, 2) rejecting pressure, 3) not wanting to fail, and 4) doing activities in their spare time. This study concludes that adolescents who have good coping strategies will be able to adapt to the urge to engage in risky sexual behavior in boarding houses. This study recommends increasing parental and community control and increasing the role of community nurses through adolescent health programs in the community, such as teenage health posts and Adolescent Health Care programs in schools.